2018
DOI: 10.1158/1055-9965.epi-17-0158
|View full text |Cite
|
Sign up to set email alerts
|

RAZOR: A Phase II Open Randomized Trial of Screening Plus Goserelin and Raloxifene Versus Screening Alone in Premenopausal Women at Increased Risk of Breast Cancer

Abstract: Background: Ovarian suppression in premenopausal women is known to reduce breast cancer risk. This study aimed to assess uptake and compliance with ovarian suppression using the luteinizing hormone releasing hormone (LHRH) analogue, goserelin, with add-back raloxifene, as a potential regimen for breast cancer prevention. Methods: Women at ≥30% lifetime risk breast cancer were approached and randomized to mammographic screening alone (C-Control) or screening in addition to monthly subcutaneous in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…In fact, the available studies on this issue date back 30 years [41][42][43][44], do not involve breast cancer patients specifically, and show conflicting results. While the majority of them generally confirm an absence of lipid-related side effects in the treatment with GnRH analogues [45], an early prospective study found that GnRH analogues significantly increased total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) [46]. In a 2004 trial enrolling 100 premenopausal women with symptomatic uterine leiomyomas, the authors compared the metabolic effects of GnRH analogues alone or in combination with raloxifene, a selective estrogen receptor modulator [47].…”
Section: Lipid Metabolism and Dyslipidemiamentioning
confidence: 97%
“…In fact, the available studies on this issue date back 30 years [41][42][43][44], do not involve breast cancer patients specifically, and show conflicting results. While the majority of them generally confirm an absence of lipid-related side effects in the treatment with GnRH analogues [45], an early prospective study found that GnRH analogues significantly increased total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) [46]. In a 2004 trial enrolling 100 premenopausal women with symptomatic uterine leiomyomas, the authors compared the metabolic effects of GnRH analogues alone or in combination with raloxifene, a selective estrogen receptor modulator [47].…”
Section: Lipid Metabolism and Dyslipidemiamentioning
confidence: 97%